Pandangan Dunia William Faulkner dalam Cerpen A Rose For Emily (Kajian Strukturalisme Genetik Lucien Goldmann) - Kahar Dwi Prihantono (JENTERA: Jurnal Kajian Sastra, 2021)
This study aimed to reveal William Faulkner’s world view (vision du monde) in a short story: A Rose for Emily (ArfE). This study applied a dialectical method and a structuralism genetic approach. Issues discussed in this study covered (1) short story structure; (2) William Faulkner's world view; (3) social structure; and (4) social groups represented by authors. Data research in sentences or paragraphs, dialogues, and monologues is available in William Faulkner’s ArfE. Based on the analysis, the writer found relationships of cultural,  natural, and human oppositions. Cultural opposition was characterized by a domination of modern town people’s attitude on conservative town person. Social opposition could be seen in the opposition between town people and Miss Emily. While, human opposition was represented by modern-communal town people and the individual person of Miss Emily. The structure of ARfE expressed both modern and humanism world views. Through the character of town people (as narrators), William Faulkner did not directly present a rejection on Old South conservative values as they were contradicted with ideal humanism values, e.g., the exaltation of past time aristocratic social status that was not in accordance with the modern time. The world view William Faulkner projected was the rise of a new nation in one flag of the Union in order to build America based on equality. Hence,  any repression of other people in terms of their social status would never occurred. This short story was written around 1929 until 1930, the social structure of the South community was hit by bankruptcy due to the Civil War and the community struggled in the Reconstruction Era until the Great American Depression era. By applying a dialectical method, the writer discovered homology between the short story’s structure and the social structure in which the story occurred. Next, the homology expressed Faulkner’s world view of modern humanism. To strengthen his worldview, Faulkner presented an interaction between modern humanism and traditional antisocial ideologies. Care to other people might build interpersonal communication that could minimalize any necrophiliac cases experienced by Miss Emily. AbstrakPenelitian ini bertujuan memperoleh pemahaman tentang pandangan dunia William Faulkner dalam cerpen “A Rose for Emily” (ArfE). Penelitian ini menggunakan metode dialektik dengan pendekatan strukturalisme genetik. Masalah yang dibahas mencakupi (1) struktur cerpen; (2) pandangan dunia William Faulkner; (3) struktur sosial, dan kelompok sosial yang diwakili oleh pengarang. Data penelitian berupa kalimat atau paragraf, dialog, dan monolog yang terdapat dalam cerpen ArfE karya William Faulkner. Berdasarkan analisis struktur cerpen, penulis menemukan relasi oposisi kultural, oposisi sosial, oposisi alamiah, dan oposisi manusia. Oposisi kultural ditandai sikap manusia modern mendominasi dan mengalahkan manusia konservatif. Oposisi sosial terlihat dari oposisi warga kota dan Miss Emily. Sementara oposisi manusia diwakili penduduk kota yang modern dan Miss Emily yang individual. Struktur cerpen ARfE mengekspresikan pandangan dunia yang modern dan humanis. Lewat tokoh penduduk kota (sebagai pencerita), William Faulkner secara tidak langsung menolak keras konservasi nilai Old South karena bertentangan dengan nilai-nilai kemanusiaan yang ideal, sebagaimana pengagungan status sosial aristokrat di masa lalu sudah tidak sesuai lagi dengan perkembangan zaman. Pandangan dunia yang ditampilkan William Faulkner adalah bangkitnya bangsa baru dalam satu bendera Union untuk membangun Amerika dengan kesetaraan derajat sehingga tekanan terhadap manusia atas status sosialnya tidak terjadi lagi. Cerpen ini ditulis sekitar tahun 1929 s.d. 1930, struktur sosial masyarakat selatan sedang dilanda kebangkrutan akibat Civil War dan masyarakat sedang berjuang di era Rekonstruksi sampai dengan era American Great Depression. Dengan menggunakan metode dialektik, penulis menemukan homologi antara struktur cerpen dengan struktur sosial tempat cerpen tersebut dilahirkan yang membentuk pandangan dunia William Faulkner dalam mengekspresikan pandangan dunia humanisme modern. Untuk menguatkan pandangan tersebut, Faulkner menggambarkan persentuhan humanisme modern dengan tradisional antisosial. Kepedulian dengan sesama manusia membuka peluang komunikasi antarindividu sehingga memperkecil peluang kasus nekrofilia seperti yang dialami Miss Emily.